Increased Interleukin-23 in Hashimoto’s Thyroiditis Disease Induces Autophagy Suppression and Reactive Oxygen Species Accumulation - Zheng, Tingting; Xu, Chengcheng; Mao, Chaoming; Mou, Xiao; Wu, Fei; Wang, Xuefeng; Bu, Ling; Zhou, Yuepeng; Luo, Xuan; Lu, Qingyan; Liu, Hongli; Yuan, Guoyue; et al. (Frontiers in Immunology, 2018)
Hashimoto’s thyroiditis (HT) represents the most common organ-specific autoimmune disease. Inflammatory factors and Reactive Oxygen Species (ROS) play detrimental roles during the pathogenesis of HT. In this study, we found that thyroid follicular cells (TFCs) from HT patients expressed an elevated level of interleukin-23 (IL-23), which contributed to autophagy suppression and ROS accumulation. Additionally, IL-23-induced autophagy suppression and ROS accumulation in human TFCs was attributed to AKT/mTOR/NF-κB signalling pathway activation. Inhibition of either IL-23 by a specific neutralization antibody, or mTOR by rapamycin, or NF-κB by IKK-16, significantly reversed the autophagy suppression and ROS accumulation. These results demonstrate a key role for IL-23 in HT pathogenesis and provide a potential therapeutic strategy against IL-23 or its signalling pathway in HT.